Optimization of Temperature and Drying Time of Protein and Fat Levels of Black Soldier Fly (Hermetia illucens) Larvae - Alya Namira, Anggi; Febrianto Mulyadi, Arie; Fitriana Subekti, Indah; Hidayat, Nur (Ann Publisher, 2024)
Hermetia illucens larvae have a high potential for treating waste as a feed ingredient rich in protein and fat. This research aims to determine the optimum temperature and drying time conditions to produce optimal yield, fat, and protein content. This research used the Response Surface Methodology (RSM) method with a Central Composite Design (CCD) design. This research uses two factors: a drying temperature of 60 - 800C and a drying time of 12 - 24 hours. The response variables measured were yield, fat content, and protein content. The research showed that a drying temperature of 720C for 12 hours provided an optimal solution for a yield of 26.23%, a crude fat content of 32.25%, and a crude protein content of 25.26%.